Hakikat Manusia Sebagai Makhluk Pedagogik - Muhammad Alqadri Burga (Madrasah Tsanawiyah DDI Cilellang, 2019)
This study aimed to analyze the essence of humans as pedagogic beings by focusing on optimizing fitrah, hearing, sight, and heart as human basic potential, as well as the implications of these various potentials for Islamic education. This study is a literature study whose data comes from documents and analyzed using content analysis method. The results of the study indicate that optimizing fitrah as a basic human potential must be through education and the creation of a conducive environment. Optimization of hearing, sight, and heart as a basic human potential by always directing it to respond to empirical stimuli not only to something that is material in nature but also to something that brings it closer to God. The essence of humans as pedagogical beings has implications for (1) the Islamic education system must be built on the integration between qalbiyah and aqliyah education; (2) Islamic education must be directed at being able to carry out the functions and objectives of the creation of humans (khalifah and ‘abd).